2001
DOI: 10.1159/000046065
|View full text |Cite
|
Sign up to set email alerts
|

Mizoribine Ameliorates the Tubulointerstitial Fibrosis of Obstructive Nephropathy

Abstract: Mizoribine has been shown to possess an immunosuppressive action that inhibits the proliferation of lymphocytes selectively by interfering with inosine monophosphate dehydrogenase. Recent studies have demonstrated that mizoribine improves renal tubulointerstitial fibrosis in the rat model of unilateral ureteral obstruction (UUO) by inhibiting the infiltration of macrophages. We, therefore, examined the dose dependency of the suppressive effect of mizoribine on the infiltration of interstitial macrophages and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…MZR treatment decreases macrophage infiltration, OPN, and TGF-beta expression and this is associated with improved histopathology, in an animal model of unilateral ureteral obstruction (5). Although, in our study, MZR treatment did not significantly suppress OPN mRNA expression in the rats receiving CsA, a tendency to decrease the OPN level seemed to be accepted.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…MZR treatment decreases macrophage infiltration, OPN, and TGF-beta expression and this is associated with improved histopathology, in an animal model of unilateral ureteral obstruction (5). Although, in our study, MZR treatment did not significantly suppress OPN mRNA expression in the rats receiving CsA, a tendency to decrease the OPN level seemed to be accepted.…”
Section: Discussioncontrasting
confidence: 64%
“…Recent studies have demonstrated that MZR suppresses the infiltration of macrophages, which play an important role in the development of interstitial fibrosis and ameliorate the interstitial fibrosis of obstructive nephropathy in rats (4,5). However, its effect has not yet been reported in the CsAtreated rat kidney.…”
mentioning
confidence: 99%
“…[27][28][29] Recently, Tanaka et al reported MZR attenuates renal injury and intraglomerular infiltration of macrophages in patients with severe lupus nephritis. 30) It is suggested that MZR inhibits MCP-1 production by GEC and may block the infiltration of intraglomerular macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its immunosuppressive effects, MZR has recently been reported to suppress the progression of histologic chronicity in selected patients with lupus nephritis and IgA nephropathy (Kawasaki et al, 2004;Tanaka et al, 2007b and c;Ikezumi et al, 2008). Moreover, MZR has been reported to attenuate tubulointerstitial fibrosis in a dosedependent manner in rat models of unilateral ureteral obstruction, non-insulin-dependent diabetes and peritoneal fibrosis via suppression of macrophage infiltration of the interstitium (Sato et al, 2001;Kikuchi et al, 2005;Takahashi et al, 2009). Interestingly, MZR has been reported to bind specifically to heat shock protein (HSP) 60, which results in interference of the chaperone activity of HSP60 in vitro (Itoh et al, 1999).…”
Section: Mizoribine a Selective Inhibitor Of Inosine Monophosphate Dmentioning
confidence: 99%